Frejdigt Mod i Jesu Navn! - Perlt, Michael (Dansk Teologisk Tidsskrift, 2013)
Collective self-understanding, in which the making of history and narratives is crucial, is not unproblematic. A shared history and myths belonging to a certain group and a historical territory, are vital ingredients in the construction and forging of narratives and collective identity. This paper aims to trail the interplay between social performance and the construction of narratives in times of crisis. The combination of memory, performance, and crisis is exemplifi ed through a sermon held by Ludvig Helveg in Odense on Palm Sunday 1864 at the time of the 2nd War of Schleswig-Holstein. As the French psychiatrist Pierre Janet has said: “Memory is an action, essentially, it is the action of telling and staging a story”. The staging of social performances serves to secure and strengthen a collective consciousness in the interplay between the interpretation of the past, understanding of the present, and expectations of the future.